Hippocampal amnesia impairs all manner of relational memory - Konkel, Alex; Warren, David E.; Duff, Melissa C.; Tranel, Daniel; Cohen, Neal J. (Frontiers in Human Neuroscience, 2008)
Relational memory theory holds that the hippocampus supports, and amnesia following hippocampal damage impairs, memory for all manner of relations. Unfortunately, many studies of hippocampal-dependent memory have either examined only a single type of relational memory or conflated multiple kinds of relations. The experiments reported here employed a procedure in which each of several kinds of relational memory (spatial, associative, and sequential) could be tested separately using the same materials. In Experiment 1, performance of amnesic patients with medial temporal lobe damage was assessed on memory for the three types of relations as well as for items. Compared to the performance of matched comparison participants, amnesic patients were impaired on all three relational tasks. But for those patients whose MTL damage was limited to the hippocampus, performance was relatively preserved on item memory as compared to relational memory, although still lower than that of comparison participants. In Experiment 2, study exposure was reduced for comparison participants, matching their item memory to the amnesic patients in Experiment 1. Relational memory performance of comparison subjects was well above amnesic patient levels, showing the disproportionate dependence of all three relational memory performances on the integrity of the hippocampus. Correlational analyses of the various task performances of comparison participants and of college-age participants showed that our measures of item memory were not influenced significantly by memory for associations among the items.